2021
DOI: 10.1111/bjh.17872
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapies for immune thrombocytopenia

Abstract: Summary Current therapies for immune thrombocytopenia (ITP) are successful in providing a haemostatic platelet count in over two‐thirds of patients. Still, some patients have an inadequate response and there is a need for other therapies. A number of novel therapies for ITP are currently being developed based upon the current pathophysiology of ITP. Many therapies are targetted at reducing platelet destruction by decreasing anti‐platelet antibody production by immunosuppression with monoclonal antibodies targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 147 publications
(268 reference statements)
0
11
0
5
Order By: Relevance
“…It has been found that classical complement pathway can be activated by platelet autoantibodies and lead to the development of ITP (56)(57)(58), and complement activation is strongly associated with the severity of ITP (59). Therefore, complement pathway have become a new target for the treatment of ITP, and clinical trials have proven that classical complement pathway inhibitors can improve platelet counts in patients with chronic ITP with rapid and durable responses (60,61). These fully illustrate that the complement pathway plays an important role in the pathogenesis of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that classical complement pathway can be activated by platelet autoantibodies and lead to the development of ITP (56)(57)(58), and complement activation is strongly associated with the severity of ITP (59). Therefore, complement pathway have become a new target for the treatment of ITP, and clinical trials have proven that classical complement pathway inhibitors can improve platelet counts in patients with chronic ITP with rapid and durable responses (60,61). These fully illustrate that the complement pathway plays an important role in the pathogenesis of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…TPO-RAs mimic the physiological actions that human TPO would perform in a healthy person [ 15 , 16 ]. Currently, four of them are approved worldwide: romiplostim, eltrombopag, avatrombopag and lusutrombopag, although the latter is indicated only for patients with chronic liver disease who are undergoing invasive procedures [ 17 , 18 , 19 ]. There is a fifth TPO-RA under development in China, the so-called hetrombopag olamine, which will be addressed in the next section.…”
Section: Currently Approved Treatments To Manage Itpmentioning
confidence: 99%
“…Immunomodulatory agents, such as mycophenolate mofetil, cyclosporin A or hydroxychloroquine, other steroids such as danazol, nucleic acid synthesis inhibitors such as azathioprine, and antibacterial agents such as dapsone or cell growth inhibitors such as vincristine, vinblastine or cyclophosphamide may be considered if the first- and second-line choices were not effective or induced non-acceptable adverse events. Nevertheless, their low rates of complete response, as well as the risk of severe side effects, preclude their widespread use [ 17 , 18 ]. Details about the management of some of them are shown in Supplementary Table S2 .…”
Section: Currently Approved Treatments To Manage Itpmentioning
confidence: 99%
“…Rövidítések BTK = Brutontirozinkináz; COVID-19 = (coronavirus dis ease 2019) koronavírusbetegség 2019; CP = (complement pathway) komplementútvonal; EMA = (European Medicines Agency) Európai Gyógyszerügynökség; FcRn = (neonatal Fc receptor subunit) neonatalis Fcreceptoralegység; FDA = (U.S. Food and Drug Administration) az Amerikai Egyesült Államok Élelmiszerbiztonsági és Gyógyszerészeti Hivatala; IgG, IgA, IgM = G, A, Mtípusú immunglobulinalosz tályok; ITP = idiopathiás (immun)thrombocytopenia (BNO: idiopathiás thrombocytopeniás purpura); Th = (helper T cell) segítő Tsejt; TPORA = thrombopoetinreceptoragonista (thrombopoetinanalóg); Treg = (regulatory T cell) regulatori kus Tsejt A klasszikus Harringtonféle felismerés [1] óta a felnőtt kori krónikus idiopathiás thrombocytopeniás purpura -ismert rövidítéssel: ITP -nemcsak idiopathiás, hanem immunpatomechanizmusú betegséggé vált, melyben a thrombocytákra lazán kötődő antitestek szerepe vilá gossá vált, s ez az eltérés lett a magyarázata a thrombo cyták gyors sequestratiójának. Ennek megfelelően a ke zelés a standard vagy emelt dózisú szteroid (prednizolon, metilprednizolon, dexametazon ), mely általában jó ko rai, de többnyire átmeneti thrombocytaszámjavulást váltott ki, vagy gyakran a tartós szteroidalkalmazás mel lékhatásai alakultak ki [2]. Ha a szteroidra adott válasz elmaradt, vagy nem volt tartós, akkor a második vonalba került a splenectomia, jó esetben 70%os hatékonyság gal (ez már nem immunmechanizmus, hanem a sequest ratióban meghatározónak vélt, amúgy normális szerv eltávolítása) [3,4].…”
unclassified
“…Ha a szteroidra adott válasz elmaradt, vagy nem volt tartós, akkor a második vonalba került a splenectomia, jó esetben 70%os hatékonyság gal (ez már nem immunmechanizmus, hanem a sequest ratióban meghatározónak vélt, amúgy normális szerv eltávolítása) [3,4]. A makrofágútvonalblokkolással (te hát nem az elsődleges immunreakcióra hatva) adjuk a nagy dózisú vénás immunglobulint (mely sajnos átme neti hatású), illetve bizonyos esetekben, főleg a tenge rentúlon, az Rhvércsoport antigénellenes megközelíté sen alapuló kezeléseket (mindkettő kényesebb kérdés a COVID-19pandémia idején, illetve az utóbbi már ott sem történik) [2,3]. A fenti kezelések csak részben cé lozzák a betegség okát, annak ellenére, hogy hatásosak lehetnek.…”
unclassified